2019
DOI: 10.1088/1361-651x/ab43fc
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanisms of electroplasticity from a crystal plasticity perspective

Abstract: Electroplasticity is defined as the reduction in flow stress of a material undergoing deformation on passing an electrical pulse through it. The lowering of flow stress during electrical pulsing has been attributed to a combination of three mechanisms: softening due to Joule-heating of the material, de-pinning of dislocations from paramagnetic obstacles, and the electron-wind force acting on dislocations. However, there is no consensus in literature regarding the relative magnitudes of the reductions in flow s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…However, the effect of electron wind is considered lower than Joule heating [ 17 ]. Using a numerical approach, Lahiri [ 18 ] showed that the effect of the electron wind force is negligible. Both Molotskii and Lahiri proposed the de-pinning of dislocation via the magnetic field that is generated while the current is flowing in the conductor [ 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of electron wind is considered lower than Joule heating [ 17 ]. Using a numerical approach, Lahiri [ 18 ] showed that the effect of the electron wind force is negligible. Both Molotskii and Lahiri proposed the de-pinning of dislocation via the magnetic field that is generated while the current is flowing in the conductor [ 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using a numerical approach, Lahiri [ 18 ] showed that the effect of the electron wind force is negligible. Both Molotskii and Lahiri proposed the de-pinning of dislocation via the magnetic field that is generated while the current is flowing in the conductor [ 17 , 18 , 19 ]. However, both these studies were undertaken using face-centered cubic (fcc) metals; this study proves that the effect of an induced magnetic field on plasticity is also observable in hcp metals.…”
Section: Resultsmentioning
confidence: 99%
“…Three wellknown theories for EAF, that is, Joule heating, depinning of dislocations, and the electron wind force, were explored individually in the case of their effect on stress drop. [7] Dislocation density-based CP model. Open-source CP software DAMASK were used for simulations.…”
Section: Key Elements Simulation Approach Findingsmentioning
confidence: 99%
“…A CP model can provide an understanding of the nature and magnitude of the reductions in flow stress due to different causative factors, including the depinning of dislocations, the electron wind force, and Joule heating, but there are some drawbacks that should be properly addressed for the widespread application of the CP. According to the study by Lahiri et al, [7] the model lacks the generality and should be modified for other…”
Section: Key Elements Simulation Approach Findingsmentioning
confidence: 99%
See 1 more Smart Citation